2000
DOI: 10.1046/j.1365-2141.2000.01956.x
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte‐derived dendritic cells do not proliferate and are not susceptible to retroviral transduction

Abstract: Dendritic cells may be generated ex vivo from CD34+ progenitor cells or peripheral blood mononuclear cells. Initial reports suggested that monocyte-derived dendritic cells (MoDCs) arise from a proliferating precursor and several groups subsequently reported successful retroviral transduction of these cells, again implying that cell division occurs. As this is of importance in the development of immunotherapy protocols, we investigated whether monocytes proliferate as they differentiate into MoDCs and also thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 21 publications
3
43
0
Order By: Relevance
“…In addition to NOTCH signaling, a diverse set of signaling events, including the PI3K/AKT and MAPK pathways, as well as the active heterodimer p50/p65 form of nuclear factor-B (NF-B), have been suggested to play a central role in maturation of DCs by inducing expression of a variety of genes involved in maturation processes (45)(46)(47)(48). In this regard, engagement of TLR2 and NOD receptors triggered the activation of the PI3K pathway under CTLA-4-or TGF-␤-triggered immunosuppressive conditions as evaluated by phosphorylation status of p85, GSK-3␤, and 4EBP1 (Figs.…”
Section: Notch1-pi3k Signaling Dynamics Integrated Into Signaling Cohmentioning
confidence: 99%
“…In addition to NOTCH signaling, a diverse set of signaling events, including the PI3K/AKT and MAPK pathways, as well as the active heterodimer p50/p65 form of nuclear factor-B (NF-B), have been suggested to play a central role in maturation of DCs by inducing expression of a variety of genes involved in maturation processes (45)(46)(47)(48). In this regard, engagement of TLR2 and NOD receptors triggered the activation of the PI3K pathway under CTLA-4-or TGF-␤-triggered immunosuppressive conditions as evaluated by phosphorylation status of p85, GSK-3␤, and 4EBP1 (Figs.…”
Section: Notch1-pi3k Signaling Dynamics Integrated Into Signaling Cohmentioning
confidence: 99%
“…Inhibition of NF-B blocks DC antigen presentation both in vitro and in vivo (6)(7)(8)(9)27), and inhibition of relB results in the generation of IL-10-producing regulatory T cells and antigenspecific tolerance in vivo (28). Indeed, many immunological adjuvants share their ability to activate NF-B among their multiple actions, but are often limited in use by their lack of specific, localized, and coordinated effects, and consequently by toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations have demonstrated that the transcription factor NF-B is essential for optimal DC function as inhibition of NF-B or its upstream activator I B kinase 2 (IKK2) blocks DC antigen presentation both in vitro and in vivo (6)(7)(8)(9). Several immunological adjuvants have been shown to activate NF-B among their multiple actions, but they are, however, limited in use by their lack of specific, localized, and coordinated effects and consequently by toxicity (10).…”
mentioning
confidence: 99%
“…LPS has been shown to activate multiple signaling pathways in dendritic cells, including p38 SAPK and ERK (23). Activation of these kinases is associated with their phosphorylation and can be detected by Western blotting using phosphorylation-specific antibodies.…”
Section: Blocks the Release Of The Pro-inflammatory Cytokines And Impmentioning
confidence: 99%